Strategi Pengembangan Usaha Penyulingan Minyak Atsiri Serai Wangi (Citronella Essential Oil) Studi Kasus : Koperasi Pandawa Pilangsari Kabupaten Majalengka - Elsa Novitasari; Wagiono Wagiono; Yeni Sari Wulandari (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2023)
Citronella oil is one of the essential oil commodities that has high market potential and many benefits. The Pandawa Pilangsari Cooperative of Majalengka Regency is a company that develops a business of refining citronella oil. The production of citronella oil at the Pandawa Pilangsari Cooperative in 2022 has increased and decreased due to the shortage of raw materials.. The purpose of this study is to analyze business processes and business models to obtain alternative business development strategies. This research uses a method to create a new business strategy, namely SWOT analysis. The results of this study show the business position in the swot quadrant I diagram, namely with an IFAS value of 3.02 and an EFAS value of 3.22 with the results of supporting an aggressive strategy. In perfecting the business of the Pandawa Pilangsari Cooperative, it implements the Strengths-Opportunities (S-O) strategy.